Improvement of Technology of Gypsum Production Raw Materials and Products in Production (Texas Journal of Multidisciplinary Studies, 2022)
Gypsum materials are one of the most effective and promising types of building materials, the production of which currently requires expansion and modernization, taking into account the latest achievements of science. This article focuses on the production of gypsum products and the improvement of production technology